ANALISIS KOOPERATIF GADUH TERNAK KAMBING MENURUT EKONOMI ISLAM DI KABUPATEN TULUNGAGUNG - Suksesiyah, Putri Kumula; Santi, Mei (LPPM STAI Muhammadiyah Probolinggo, 2024)
The livestock rearing system, known as gaduh goats, is when capital owners or investors have goats and hand them over to other parties to care for them, and are given compensation in the form of profit sharing. In this research, researchers will examine the cooperative analysis of rowdy goat farming according to Islamic Economics in Pojok Village, Ngantru District, Tulungagung Regency. This research intends to analyze cooperative rowdy goat farming according to Islamic Economics. The method applied is a descriptive qualitative approach intended to analyze data in the form of words and images. The types of data processed are primary and secondary data. Primary data was collected directly in the field, namely through owners and breeders, while secondary data was obtained from books and online journals. Data collection applies observation, interview, and documentation techniques. The concept of profit sharing aims to organize partnerships to bear risks and obtain business results for both parties. In this system, there is no guarantee of fixed profits, and profits and losses are shared according to the initial agreement. This principle avoids the element of uncertainty that includes ordinary business risks, but not excessive uncertainty (gharar), which is not permitted in Islam. Risk management in this noisy system is by the principles of Islamic Economics, where future risks are borne by all parties. Keyword: Goat Rowing Practice, Cooperative, Profit Sharing.